Social representations and valorial orientations: the immigrants case (Memorandum: Memória e História em Psicologia, 2011)
The principal idea of this paper can be divided in two macro axes: the first is that the behavior toward the other or others, above all, depends on the representation that people build as to him/them, on the interpretations of actions (pasts, presents, and futures), and on the landmark of socio-cultural context. When responsibilities are attributed to an individual or to a group for critical and /or of sufferance conditions, the situation produced is that it is attributed a false fault to a subject or to a group that could be recognized as “enemy”. The second is that images transmitted by the media do not produce only symbolism that contributes to the self construction of the identity, but provide identification models too on which it is possible to find interactions and social actions. In the specific case of the research we present modifications in the perceptions of young people who took part in the research, in regard to immigrants, they allow to look at a different direction that could assume a positive valence (making more familiar what was distant). But it is right to underline that in other situations images produce contrary effects and rather liberate from a stereotyped conditioning than push the subject to reinforce such position.